Identification techniques and culture media for the growth of Bacillus thuringiensis used to control vector mosquitoes: Mini review (Research, Society and Development, 2021)
Bacillus thuringiensis (Bt) is a bacterium of worldwide interest, due to its high toxicity to a wide range of insect vectors of pathogens to humans and agricultural pests. The insecticidal action of Bt is conferred by the presence of protein crystals, which act as toxins. Several studies are carried out in order to select Bt strains from different ecosystems with mosquitocidal action for vector insects. It is observed that the soil is the most used substrate for the isolation of Bt, being widely found in nature, predominantly in the form of spores. The search for new Bt strains in different regions of the world aims to obtain new toxins with insecticidal action, which can be used in the production of biopesticides. For the cultivation of the strains, Nutrient Agar or NYSM media are used. Culture media have a wide variety of nutrients, being rich in carbon, nitrogen and mineral salts, which are used to induce the growth of microorganisms. Therefore, several studies seek to improve these means for the growth of Bt, using alternative effective and economical means, the control of vector mosquitoes.